2010
DOI: 10.1097/jto.0b013e3181fd42eb
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Phase II Trial of Pemetrexed and Carboplatin with or without Enzastaurin versus Docetaxel and Carboplatin as First-Line Treatment of Patients with Stage IIIB/IV Non-small Cell Lung Cancer

Abstract: There was no difference in TTP between the three arms, but survival was longer with pemetrexed-carboplatin compared with docetaxel-carboplatin. Enzastaurin did not add to the activity of pemetrexed-carboplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…In addition, limited evidence showed that the risk of grade 3/4 epistaxis was higher in PKC inhibitor-chemotherapy group (5.9 %) than chemotherapy alone group (1.2 %) (P = 0.022) [19]. Incidence of renal failure, hypokalemia, weight loss, hypertension, and diarrhea was similar between PKC inhibitors-chemotherapy groups (0.6, 2.8, 1.9, 12.5, 4.2 %) and chemotherapy groups (1.2, 0.6, 0.6, 22.2, 1.4 %) [11,18,19].…”
Section: Adverse Effectsmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, limited evidence showed that the risk of grade 3/4 epistaxis was higher in PKC inhibitor-chemotherapy group (5.9 %) than chemotherapy alone group (1.2 %) (P = 0.022) [19]. Incidence of renal failure, hypokalemia, weight loss, hypertension, and diarrhea was similar between PKC inhibitors-chemotherapy groups (0.6, 2.8, 1.9, 12.5, 4.2 %) and chemotherapy groups (1.2, 0.6, 0.6, 22.2, 1.4 %) [11,18,19].…”
Section: Adverse Effectsmentioning
confidence: 57%
“…After reviewing the remaining six trials, we excluded one trial because of maintenance treatment with PKC inhibitor. Finally, five relevant RCTs, comprising a total of 1,005 patients, were included [10,11,[17][18][19]. The five RCTs contained the following two PKC inhibitors: enzastaurin (an inhibitor of PKC-b) and aprinocarsen (a PKC-a antisense oligonucleotide).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also suggest that enzastaurin is tolerable when administered with full-dose cytotoxic chemotherapy, but because of the lack of additional efficacy with enzastaurin in the aforementioned studies [13,14], our patients remained in the study but continued treatment with cisplatin-pemetrexed or an alternative therapy of the physician’s choice.…”
Section: Discussionmentioning
confidence: 66%
“…The addition of enzastaurin to cisplatin/pemetrexed as first-line treatment in patients with advanced NSCLC was well tolerated, with no new or unexpected safety issues observed, and showed preliminary activity in the safety lead-in phase with 8 partial responses (1 unconfirmed). However, on the basis of the interim results from two other phase II, randomized trials of enzastaurin in patients with NSCLC [13,14], we decided to terminate the study early. These studies showed that the addition of enzastaurin to pemetrexed and to carboplatin-pemetrexed was well tolerated, with no new safety issues identified, but did not provide additional efficacy in patients with advanced NSCLC, and both studies were subsequently closed.…”
Section: Discussionmentioning
confidence: 99%